Crafting the landscape photograph with Lightroom Classic and Photoshop techniques for realizing the full potential of your photography - Willmore, Ben (Rocky Nook, 2023)
Realize the full potential of your photography and produce breathtaking landscape images using Lightroom Classic and Photoshop! You can follow all the tried-and-true rules of great landscape photography--shooting in great light, making sure to have a clear subject in the scene, and maximizing sharpness throughout the image--and yet your photos can still somehow fall flat. Compared to others' work you see online or in print, there just seems to be something missing: your images are a bit bland, while others' work is often inspiring, lively, and beautiful. What gives? The difference can often be found in the photographer's post-processing techniques in Lightroom Classic and Photoshop that they use to help direct the viewer's eye and make their images come alive. This kind of post-processing is not about "fixing mistakes" but is an essential part of the successful landscape photographer's contemporary workflow. Photographer and author Ben Willmore has spent over 30 years refining his own images and workflow, written more than a dozen books, and led photo workshops around the world. All in all, he has taught more than 100,000 photographers in person, so he knows the questions, concerns, and frustrations that landscape photographers have. In this book, you'll learn how to use Lightroom Classic and Photoshop in order to transform your captures into something you can truly be proud of. From shooting techniques that help you capture the most robust RAW file at the highest quality possible to developing your images in Lightroom Classic and Photoshop, Ben covers global and local adjustments, masking, selections, layers, color, luminance, sharpness, multi-image composites, focus stacking, and much more. Topics include: • Idealized color and color grading • Detail and sharpness • Separation and depth • Establishing balance • Creating compelling contrast • Leading the eye • Dodging and burning • Black and white • Eliminating artifacts and distractions • Adding emotion • Producing a coherent body of work • Panoramas and HDR Ben teaches you not only about "learning the tools" but about applying these tools to your work in such a way that you can direct the viewer's eye through your photograph via the use of contrast, brightness, color, tone, framing, and detail. By learning how to use and apply these techniques to your own work in an intentional, expressive way, you'll be equipped to elevate your work and finally make the kinds of landscape photographs you've always wanted to make. TABLE OF CONTENTS Part 1: Accumulate Expertise Chapter 1: Develop a Lightroom + Photoshop Mindset Chapter 2: Working in Lightroom Classic Chapter 3: Working in Photoshop Part 2: Quality Considerations Chapter 4: Eliminate Shooting Artifacts Chapter 5: Extend Potential with Multiple Exposures Chapter 6: Eliminate Processing Artifacts Part 3: Essential Techniques Chapter 7: Lead the Eye Chapter 8: Add Dimension, Atmosphere, & Drama Conclusion.